APPLICATION OF THE SCAFFOLDED READING METHOD TO IMPROVE STUDENTS’ READING COMPREHENSION AT SMKN 6 MAKASSAR - Teken, Rhima Novelin; Talib, Ahmad; G., Hasriani (State University of Makassar, 2025)
This research aims to improve the reading comprehension of students at SMKN 6 Makassar using the scaffolded reading method. The research method used was pre-experimental with one experimental group. The research subject was class XI fashion 3 as the experimental group. The research data is collected by test. The experimental group was given a pre-test and post-test to measure students' abilities in reading comprehension. The population of this research was class XI students majoring in Fashion at SMKN 6 Makassar. The sample of this research was 33 students of class XI Fashion 3. The results of this research is significance score for the learning outcome variable is 0.000 which is lower than significance degree is <0.05. It can be concluded there is a significant influence of using scaffolded reading method on the reading comprehension.Keyword: Reading Comprehension, Scaffolded Reading Method